2006
DOI: 10.1109/iccad.2006.320025
|View full text |Cite
|
Sign up to set email alerts
|

A New Paradigm for Low-power, Variation-Tolerant Circuit Synthesis Using Critical Path Isolation

Abstract: Design considerations for robustness with respect to variations and low power operations typically impose contradictory design requirements. Low power design techniques such as voltage scaling, dual-Vth etc. can have a large negative impact on parametric yield. In this paper, we propose a novel paradigm for low-power variationtolerant circuit design, which allows aggressive voltage scaling. The principal idea is to (a) isolate and predict the set ofpossible paths that may become critical under process variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…For simplicity, we target only average performance for now, while this problem formulation can be easily modified to target other design objectives such as low power as in CRISTA [4], [5].…”
Section: Variable Latency Vlsi Design Methodologymentioning
confidence: 99%
See 2 more Smart Citations
“…For simplicity, we target only average performance for now, while this problem formulation can be easily modified to target other design objectives such as low power as in CRISTA [4], [5].…”
Section: Variable Latency Vlsi Design Methodologymentioning
confidence: 99%
“…A variable-latency adder may include a fast and incomplete adder including only carry chains of a length no more than k (Figure 1), and a slow and complete adder, with a predictor selecting one of the two adders [9]. This variable-latency logic design technique can be extended to other arithmetic units such as multipliers [10], and random logic blocks [4], [5].…”
Section: B Existing Variable Latency Design Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…RELATED WORK Prior work that addresses variability can be classified into (i) statistical design approaches [25] [9] [17], (ii) post silicon compensation and correction [12] [18] [32], and (iii) variation avoidance [8] [3] [11]. Our work differs in that it addresses hardware variability in the operating system layer.…”
Section: Introductionmentioning
confidence: 99%
“…The method presented in [8] allows reduction of voltage margins by dynamic supply voltage control and monitoring of the circuit error rate. It is observed that even when the circuit logic delay is marginally longer than the critical path delay of the circuit (due to supply voltage reduction), the resulting logic error rate increases marginally due to the fact that the circuit critical paths are excited infrequently by the applied stimulus [9]. As the supply voltage is decreased further, this error rate increases rapidly leading to a large deterioration in output signal quality.…”
Section: Introductionmentioning
confidence: 99%